Integrating content and language in teacher development: CLIL for academic vocabulary growth in Algeria - Tobbi, Saida (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2026)
This study investigates the impact of Content and Language Integrated Learning (CLIL) on academic vocabulary development and disciplinary understanding among newly recruited teachers at Batna 2 University, Algeria. Conducted within the framework of the national teacher development program, the research examined how integrating English into the teaching of research methodology could enhance both linguistic competence and conceptual learning. A mixed-methods framework integrated quantitative and qualitative approaches, including an Academic Vocabulary Test, a corpus of participants’ written tasks, and reflective questionnaires. Sixty-eight teachers from twenty-three academic departments participated in eight weeks of CLIL-oriented instruction. Quantitative findings revealed notable improvements in receptive and productive academic vocabulary (t(67) = 14.27, p < .001, d = 1.37), alongside marked increases in lexical diversity, sophistication, and density. Thematic analysis indicated greater lexical awareness, cognitive engagement with research concepts, and positive perceptions of English as a medium for disciplinary learning. The results suggest that CLIL-oriented pedagogy promotes deep processing of academic lexis and supports Algeria’s ongoing transition toward English-medium higher education. Embedding content and language objectives within teacher education programs can therefore strengthen linguistic competence and disciplinary literacy in multilingual academic contexts.